Investigating novel progenitor cell populations in the fish heart - Killen-Devine, AC (2018)
After cardiac injury, most mammals, including humans, cannot regenerate lost heart muscle with new, functioning cardiomyocytes. The cave-dwelling variant of A mexicanus, a species of teleost fish, is similar to humans and also cannot regenerate. Remarkably, the surface-dwelling variant of the same species can regrow damaged heart muscle, like its fellow teleost fish the zebrafish. Comparison of the surface and cave-dwelling A mexicanus fish is, therefore, a powerful method to identify new mechanisms behind the ability to regenerate, which could lead to therapeutic interventions for humans who have suffered a cardiac injury. Using this model system, comparison of cave and surface variants showed that there are variations in the levels of epicardial fat before and after cardiac injury between the fish, suggesting differential activity of a mesenchymal fat progenitor. Fat has been found to have a positive effect on injury outcome, but fatty fibrotic scar tissue is a symptom of a nonregenerative environment. Such a progenitor has not been found in the fish before, therefore efforts were made to identify it. Investigations using a mesenchymal stem cell marker, Pdgfrα, identified previously unknown populations positive for this marker in the fish heart, including one in the epicardium and another in the endocardium. Lineage tracing experiments showed that the epicardium, likely Pdgfrα-positive epicardial cells, is the source of the epicardial fat that arises during development and after injury, a process that has been previously reported in the mouse. Investigation of the identity of the endocardial population showed that some of these endocardial cells begin to express Runx1, a hematopoietic progenitor marker, after injury. The expression of hematopoietic markers in endothelial cells has been previously shown during development, where endocardial cells undergo an endothelial-to-hematopoietic transition (EHT) and detach, forming hematopoietic stem cells that give rise to the blood lineages. Transcriptomic analyses showed that the injured endocardium has upregulated expression of many key hematopoietic development genes. Live imaging experiments in cultured heart slices, a novel experimental method, show endocardial cells detaching from the myocardium after injury in a way that recapitulates the developmental EHT. These results strongly suggest that the injured fish endocardium produces hematopoietic stem cells after injury. In summary, through analysis of fish hearts, two novel injury-responsive progenitors have been identified: an epicardial fat progenitor and hematopoietic progenitors derived from the injured endocardium. These progenitors offer an exciting new avenue for investigations into the mechanisms behind the ability to repair damaged hearts.